Validation of an offshore wind atlas using the satellite data available at the coastal regions of portugal - Marujo, R. (2014)
In this study a validation methodology for regional mesoscale model simulations when ingested with surface wind data inferred from satellite sources around Continental Portugal is evaluated. Observational wind data from a “quasi” offshore anemometric mast located in the Berlenga Island – near Peniche region – was used for the validation study. Satellite sources of wind data under assessment are the ones being used in the EC funded FP7 NORSEWInD project, such as the QuikSCAT and SAR. The validation study evolves 10 years of full wind data, starting in January 2000 to December 2009. The evaluation was performed in two different spatial validation approaches. Results from this study indicate that the wind satellite data has good quality to be assimilated on high resolution mesoscale model simulations particularly the ones concerned with long term behavior of the wind field near the coastal areas.